KONVERGENSI SEBAGAI RESPON TERHADAP EPISTIMOLOGI TAFSIR IBN ASYUR TENTANG KOTA - Kholaf Al Muntadar (STIT Muhammadiyah Paciran Lamongan, 2025)
This study discusses the epistemology of Ibn 'Asyur's exegesis regarding the concept of the city in the Qur'an, with a focus on various terms such as madinah, balad, qaryah, qura, dar, ard, and misr used in the holy text. Ibn 'Asyur interprets these terms not only as representations of the physical city but also as reflections of urban social and cultural life. Through his exegesis, he integrates interdisciplinary knowledge, such as philosophy, urban sociology, and geography, in explaining the concept of the city in various physical, social, and philosophical contexts. Moreover, this study explores the relevance of Ibn 'Asyur's thinking in the context of modern urban planning and development policies, referencing the ideas of contemporary exegesis scholars like Quraish Shihab. This research provides insights into how Ibn 'Asyur's exegesis can inspire the management of cities based on religious, social, and cultural values, as well as the relevance of local context in governmental policies.